PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA, KOMPETENSI DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Restoran Pippo Italian Senayan City, Jakarta Pusat): Fakultas Ekonomi dan Bisnis, Universitas Budi Luhur Jakarta - Lestari, Dinda Mayang Dwi; Wahyudi, Widi (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
Through an in-depth quantitative approach, this study aims to test the proposed hypothesis regarding the relationship between HR development, competence, and HR quality with employee performance at Pippo Italian Restaurant Senayan City, Central Jakarta. All restaurant employees, covering various levels of positions and responsibilities, were the subjects of the research, and data were thoroughly collected through questionnaires specifically designed to measure these variables. The findings of this study clearly show that enhancing employee competence directly contributes to improving their performance across various aspects of their work. This indicates that more targeted and sustained efforts to enhance employee competence, such as through training and development tailored to their specific needs, should be a primary focus in improving overall performance at Pippo Italian Restaurant Senayan City.